Spatial variation in cervical cancer screening participation and outcomes among Indigenous and non‐Indigenous Australians in Queensland. (24th May 2018) - Dasgupta, Paramita; Whop, Lisa J.; Diaz, Abbey; Cramb, Susanna M.; Moore, Suzanne P.; Brotherton, Julia M.L.; Cunningham, Joan; Valery, Patricia C.; Gertig, Dorota; Garvey, Gail; Condon, John R.; O'Connell, Dianne L.; et al.
Abstract: Indigenous women continue to experience a disproportionately higher burden of cervical cancer than non‐Indigenous women in Australia. The National Indigenous Cervical Screening Project used probabilistic record linkage to combine population‐based administrative databases and identify Indigenous women on Pap Smear Registers. This study aimed to quantify the spatial variation by local government areas (LGAs) for Indigenous and non‐Indigenous women in Queensland in cervical screening participation rates and related outcomes. Empirical Bayes local geostatistical smoothing was performed to reduce the likelihood of spurious variation between small areas. The cohort included 1, 091, 260 women (2 per cent Indigenous) aged 20 to 69 with 2, 393, 708 Pap smears between 2006 and 2011. Indigenous women had smoothed LGA‐specific 5‐year participation rates (interquartile range (IQR) 38.9–53.3 per 100 eligible women) consistently lower than non‐Indigenous women (IQR 80.7–85.3). The non‐overlapping confidence intervals of these rates suggest that the Indigenous differential was significant. Compared with Indigenous women, non‐Indigenous women had consistently lower and more stable prevalence rates of histologically confirmed high grade abnormalities (IQR 8.0–10.1 versus 15.0–21.3 per 1, 000 screened women). Although the LGA‐specific rates also suggest that a higher proportion of non‐Indigenous women were followed‐up within two months of an abnormal screening result, the wide confidence intervals for these estimates limit our ability to draw definitive conclusions about spatial patterns for this outcome. These findings highlight the importance of continued monitoring and ongoing efforts to identify drivers of these patterns and develop effective strategies to improve participation and potentially reduce the cervical cancer burden among Indigenous women.